Molecular Characterization and Gene Expression Analysis of Aquaporin in Haemaphysalis qinghaiensis - Niu, Qingli; Hao, Rongzeng; Pan, Yuping; Liu, Zhijie; Yang, Jifei; Guan, Guiquan; Luo, Jianxun; Yin, Hong (Frontiers in Physiology, 2022)
Aquaporins (AQPs) are important functional proteins and widely present in cell membrane of almost all organisms, mediating transmembrane transport of liquid and other solutes. Much is known about the molecular characterization of AQPs in other tick species, but nothing is known about them in Haemaphysalis qinghaiensis. In this study, we first sequenced the transcript variants of AQPs in H. qinghaiensis (HqAQPs), analyzed the biological structure features of AQPs and investigated the pattern of gene expression of the AQP gene of H. qinghaiensis in different tick tissues and stages to predict their biological functions. In conclusion, four AQPs transcript variants (HqAQP1-1, HqAQP1-2, HqAQP1-3 and HqAQP1-4) of H. qinghaiensis were found and the sequences were comparable to its orthologues from reported tick species. Gene expression of AQPs in tick different tissues and stages was showed the higher expression level in salivary glands and gut of adult female, as well as in the female and nymph than in Malpighian tubules, ovary, male, larvae and egg. Further studies will be performed to evaluate the function of HqAQPs against H. qinghaiensis infestation on animals.